2019
DOI: 10.1111/petr.13340
|View full text |Cite
|
Sign up to set email alerts
|

Moderate‐severe primary graft dysfunction after pediatric heart transplantation

Abstract: Background PGD is a complication after heart transplantation (OHT) and a significant cause of mortality, particularly in infant recipients. Lack of standardized definition of PGD in the pediatric population makes the prevalence and magnitude of impact unclear. Methods ISHLT PGD consensus guidelines, which include inotrope scores and need for MCS, were applied retrospectively to 208 pediatric OHT recipients from a single institution from 1/2005‐5/2016. PGD was defined as: moderate PGD—inotrope score >10 on post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In cases where retransplantation with MCS occurred >1 year after primary transplant, 1‐ and 5‐year survival nearly matched that of retransplantation without MCS (64% and 56%, respectively) 7 . Other single‐center studies have shown similar difficulties supporting this patient population in children 1,8,9 and adults 10,11 . In a review of Organ Procurement and Transplantation Network (OPTN) data, any MCS (ECMO or VAD) prior to retransplantation predicted increased mortality during transplantation (HR 2.5 [95% CI 1.6–4.1], p < .01) 12 …”
Section: Discussionmentioning
confidence: 91%
“…In cases where retransplantation with MCS occurred >1 year after primary transplant, 1‐ and 5‐year survival nearly matched that of retransplantation without MCS (64% and 56%, respectively) 7 . Other single‐center studies have shown similar difficulties supporting this patient population in children 1,8,9 and adults 10,11 . In a review of Organ Procurement and Transplantation Network (OPTN) data, any MCS (ECMO or VAD) prior to retransplantation predicted increased mortality during transplantation (HR 2.5 [95% CI 1.6–4.1], p < .01) 12 …”
Section: Discussionmentioning
confidence: 91%
“…Perioperative management consists of some topics that are listed in Table 6 [11][12][13][14][15][16].…”
Section: Perioperative Managementmentioning
confidence: 99%
“…No difference in donor-specific factors (age mismatch, size mismatch, sex mismatch, need for cardiopulmonary resuscitation, ejection fraction, or inotrope need) was observed between patients with and without PGD. Occurrence of moderate/severe PGD correlated with significantly worse survival at both discharge (85% vs 96%, P < 0.01) and one-year posttransplant (57% vs 91%, P ¼ 0.04) [14]. A chart summarizing the findings of all pediatric studies to investigate the impact of donor-specific factors on pediatric heart transplant outcomes is included (Fig.…”
Section: Andandmentioning
confidence: 99%